SERUM LIPID AND TRACE MINERAL PROFILES AMONG TYPE 2 DIABETICS AND HYPERTENSIVE DIABETICS AT THE BAMENDA REGIONAL HOSPITAL - LUKONG HUBERT SHALANYUY; SAMJE MOSES (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Diabetes mellitus has become a clinical condition of public health importance, especially in developing countries due to its high mortality and morbidity. The aim of this study was to measure and compare the lipid and serum trace mineral profile among type 2 diabetics and hypertensive diabetics with controls. Methods: This cross-sectional study was carried out at the Regional Hospital, Bamenda, involving 50 diabetic normotensives, 50 hypertensive diabetics, and 50 normal recruited subjects. Serum levels of lipids and minerals were determined using standard methods. Results: Of the four trace elements assessed, except for copper (Cu) whose mean values in diabetics were abnormally increased (p=0.01), zinc (Zn), magnesium (Mg), and chromium (Cr) showed significantly decreased mean values in diabetics compared to the controls (p<0.05). The mean levels of these trace elements were also significantly reduced in hypertensive diabetic patients (p<0.05). In diabetics, there was no significant difference in the lipid levels. However, only total cholesterol (TC) and low-density lipoprotein mean values were significantly higher in hypertensive diabetic patients compared to the normal controls. There was also a positive significant correlation between the body mass index and Cr (r=+0.3, p=0.045) in diabetics. Conclusion: This study saw statistically significant differences in the serum lipid and trace element levels between diabetics, hypertensive diabetics, and controls: With diabetic and diabetic hypertensive patients having higher serum Cu levels and decreased serum Mg, Zn, and Cr levels compared to the normal controls. The lipid profile levels in diabetics and hypertensive diabetics were not significant differences within the study groups for all lipid profile estimations except for TC and LDL which were significantly higher only in hypertensive diabetic patients.